Neurological abnormalities among pediatric patients with sickle cell disease in Saudi Arabia: a single-center retrospective study - Basuni, Ziad T.; Monagel, Dania A.; Taha, Areej; Ahmed, Nehal; Ahmed, Amany (Frontiers in Pediatrics, 2024)
Sickle cell disease (SCD) is a common inherited blood disorder characterized by the production of abnormal sickle-shaped red blood cells. SCD can lead to various complications including neurological issues. Early detection and treatment are crucial for preventing these complications.This study aimed to describe the neurological manifestations, radiological findings, and neurological diagnosis related to SCD in Saudi children with the aim of contributing to the formulation of population-based guidelines for screening and treating SCD-related neurological complications.This descriptive retrospective study included pediatric patients aged < 14 years diagnosed with SCD who were regularly followed up at the hematology clinic in KAMC, Jeddah, Saudi Arabia, from January 2008 to January 2022. Demographic and clinical data were collected from the clinical charts of 101 participants.This study included 101 patients with SCD with a mean age of 23 months at diagnosis. Among these, 59% had SCD and high fetal hemoglobin (HbF) levels. Neurological sequelae, including seizures, stroke, and other abnormalities, were observed in 26.7% of patients. There were no significant differences in the onset of neurological issues between the patients with SCD-high HbF and those with other SCD phenotypes.